2020
DOI: 10.1101/2020.10.14.338939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information Decomposition in the Frequency Domain: a New Framework to Study Cardiovascular and Cardiorespiratory Oscillations

Abstract: While cross-spectral and information-theoretic approaches are widely used for the multivariate analysis of physiological time series, their combined utilization is far less developed in the literature. This study introduces a framework for the spectral decomposition of multivariate information measures, which provides frequency-specific quantifications of the information shared between a target and two source time series and of its expansion into amounts related to how the sources contribute to the target dyna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Such protocol should also include intermediate resting phases between stressful situations to assess whether elicited stress still produces effects during time in a consequent resting phase. Future methodological work is also envisaged regarding: (a) a thorough validation on simulations of the MI measures presented here performed also through a direct comparison with more sophisticated analysis techniques including the use of time-delayed techniques employing tools of information dynamics to retrieve directional information ( Faes et al, 2014 ) and of non-linear model free entropy estimators ( Faes et al, 2015a ); (b) the frequency-specific decomposition of the proposed measures (e.g., following Faes et al, 2020 ) to investigate how MIs can reflect oscillatory rhythms with specific physiological meaning; and (c) the analysis on source-reconstructed signals to obtain better anatomically-localized estimates of the strength and topology of brain–body interactions ( Lai et al, 2018 ; Van de Steen et al, 2019 ; Kotiuchyi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such protocol should also include intermediate resting phases between stressful situations to assess whether elicited stress still produces effects during time in a consequent resting phase. Future methodological work is also envisaged regarding: (a) a thorough validation on simulations of the MI measures presented here performed also through a direct comparison with more sophisticated analysis techniques including the use of time-delayed techniques employing tools of information dynamics to retrieve directional information ( Faes et al, 2014 ) and of non-linear model free entropy estimators ( Faes et al, 2015a ); (b) the frequency-specific decomposition of the proposed measures (e.g., following Faes et al, 2020 ) to investigate how MIs can reflect oscillatory rhythms with specific physiological meaning; and (c) the analysis on source-reconstructed signals to obtain better anatomically-localized estimates of the strength and topology of brain–body interactions ( Lai et al, 2018 ; Van de Steen et al, 2019 ; Kotiuchyi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential method comes from the equality of Granger causality and information transfer or information theoretic measure for Gaussian variables in the time and frequency domain [73,74]. Also, recent work showed that for linear Gaussian processes the information modification (one of the component of information processing) may be formulated, analytically, in the frequency domain [75,76] as the synergy component of a partial information decomposition following the idea of [77], and using the PID measure I MMI of [78]. This frequency decomposition approach for linear Gaussian processes can be also adopted for the AIS.…”
Section: Relation To Previous Approachesmentioning
confidence: 99%
“…This frequency decomposition approach for linear Gaussian processes can be also adopted for the AIS. When the assumptions of linear Gaussian processes are valid, then the methods in [71] or [75,76], will be more data-efficient and come with lower computational burden. Furthermore, the frequency estimation of the AIS for Gaussian variables will then allow for a more precise identification of the relevant frequency components (the work in [75,76], evaluates the all frequency spectrum while the current method can only identify frequency bands).…”
Section: Relation To Previous Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we introduce a framework for the evaluation of total, directed and instantaneous interactions between pairs of time series in both time and frequency domains. The framework is built on previous works establishing a connection between information-theoretic and spectral approaches to the assessment of coupling and causality (Chicharro, 2011;Faes et al, 2021), yielding time domain measures of total coupling, Granger causality and instantaneous interaction that can be retrieved by integrating the corresponding spectral measures over the whole frequency axis. Moreover, the framework is formulated in a way such that two alternative ways are provided to treat instantaneous effects in both time and frequency domains.…”
Section: Introductionmentioning
confidence: 99%